2016
DOI: 10.1186/s12974-016-0553-3
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine alters microglial immune function through P2X7R signaling

Abstract: Background: Purinoceptors have emerged as mediators of chronic inflammation and neurodegenerative processes. The ionotropic purinoceptor P2X7 (P2X7R) is known to modulate proinflammatory signaling and integrate neuronal-glial circuits. Evidence of P2X7R involvement in neurodegeneration, chronic pain, and chronic inflammation suggests that purinergic signaling plays a major role in microglial activation during neuroinflammation. In this study, we investigated the effects of methamphetamine (METH) on microglial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 87 publications
0
29
0
Order By: Relevance
“…METH has been shown to increase IL-10 in human plasma [14]. Similarly, the evaluation of METH in microglial cell (ESdM) activation showed an increased IL-10 production following 48-hr METH treatment [52]. In a comprehensive gene array overview, macrophages stimulated over a time-dependent METH dose showed considerable upregulation of IL-10 at 6 hours post METH exposure [17].…”
Section: Il-10mentioning
confidence: 91%
“…METH has been shown to increase IL-10 in human plasma [14]. Similarly, the evaluation of METH in microglial cell (ESdM) activation showed an increased IL-10 production following 48-hr METH treatment [52]. In a comprehensive gene array overview, macrophages stimulated over a time-dependent METH dose showed considerable upregulation of IL-10 at 6 hours post METH exposure [17].…”
Section: Il-10mentioning
confidence: 91%
“…Although previous studies have demonstrated methamphetamine-induced microglial activation 11 , 12 , 37 , the molecular and cellular mechanisms involved in this process are not completely understood. Therefore, we demonstrated the vital role of the sigma-1 receptor in methamphetamine-mediated microglial activation in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 97%
“…Microglia are known to be actively involved in various neurological diseases, such as Parkinson’s disease 6 , stroke 7 and depression 8 . Accumulating evidence suggests that methamphetamine-induced neurotoxicity is associated with microglial activation 9 , and activated microglia are thought to participate in either pro-toxic or protective mechanisms in the brain 10 12 . The classic M1 and alternative M2 phenotypes, which are the two most polarized phenotypes, represent two extremes of a dynamic changing state of microglial activation.…”
Section: Introductionmentioning
confidence: 99%
“…for 2 min, rinsed in distilled water to remove excess stain, and imaged. Protein levels were normalized to Po-S as a loading control (100-140 kDa) [31]. After blocking, rabbit anti-CD11b antibody (127 kDa, 1:1000, ab133357, Abcam) was incubated at 4°C overnight.…”
Section: Western Blotmentioning
confidence: 99%